El próximo escenario global de Kenichi Ohmae: ¿Mito o realidad? - Mora Casal, René Alejandro (2014)
The issue of globalization is analyzed from three points of view in this article.First, a critical analysis is made of the book The Next Global Stage by KenichiOhmae, who argues that the worldis now globalized and it is an unavoidable reality. Although Ohmae is right onseveral things, he also omits important issues, in particular the negative aspects of globalization. Secondly, the opinions of two other authors are presented, who have written about globalization: one of them is Thomas Friedman, who brings a broader vision of globalization, and the other is Pankaj Ghemawat, who is somewhat skeptical and believes that,at most, the world is semiglobalized.Third, the case of Costa Rica is analyzed,a country that decided to take the path of globalization and trade liberalization 35 years ago, a decision which has led us to experience both their positive and negative aspects.